2019
DOI: 10.7704/kjhugr.2019.19.3.174
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Helicobacter pylori Immunoglobulin G Levels and Gastric Mucosal Atrophy after Successful Eradication of Helicobacter pylori

Abstract: Background/Aims: Limited information is available about the relationship between Helicobacter pylori (H. pylori) immunoglobulin (Ig) G and serum pepsinogen (pepsinogen [PG], a marker of gastric mucosal atrophy) concentrations after H. pylori eradication. Materials and Methods: Eligible patients who underwent endoscopic submucosal dissection (ESD) for early gastric cancer from in a tertiary-referral center, and whose serum H. pylori IgG and PG concentrations were measured at the time of performing ESD and one y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous study reported negative conversion rates of 35-62% at one year from H.pylori elimination. 26,[28][29][30] It took 17.9 months for those with an intermediate level of antibody titer before eradication to convert to negative, and 42.8 months for those with a higher level. 31 Complete negative conversion was usually not observed within one year after eradication.…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%
“…Previous study reported negative conversion rates of 35-62% at one year from H.pylori elimination. 26,[28][29][30] It took 17.9 months for those with an intermediate level of antibody titer before eradication to convert to negative, and 42.8 months for those with a higher level. 31 Complete negative conversion was usually not observed within one year after eradication.…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%